Pelaksanan Tugas Camat Dalam Penyelenggaraan Ketentraman Dan Ketertiban Umum di Kecamatan Ulee Kareng Kota Banda Aceh - Akhyar Akhyar; Saifuddin Saifuddin; Nasruddin Nasruddin; Fitra Rezki (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
One of the implementation of government at the sub-district level is Camat who receives the delegation of authority as the task of the leader and coordinates with the implementation of general government duties in accordance with Government Regulation No. 17 of 2018 concerning Subdistricts, including coordinating the implementation of peace and public order especially in preventing conflict prevention including maintaining peace in the community. The purpose of this study was to determine the implementation of Camat tasks in the administration of public peace and order in the Ulee Kareng sub-district, and to find out the intensiveness related to the implementation of the Camat's tasks in organizing peace and public order in the Ulee Kareng sub-district. To obtain data in this paper used the method of library research and field research, data collection techniques from library research is done by reading the literature literature and existing laws. While the field data obtained by interviewing respondents and informants directly involved with the problem under study. The results of the research show that the Camat's task of coordinating peace and order is not yet well implemented, it is evidenced that there is no cooperation between Muspika and Gampong kechik, although meetings have been held to coordinate communication to equalize perceptions in the security of the Gampong. Forms of peace and order that unsettle the public are juvenile delinquency and drugs, for example the presence of colors that open until 4 am and there are young people as drug dealers as well as users. Meanwhile, as the administrator of the sub-district administration's duty, it still requires guidance and supervision of the administration of the village administration including regulations, which have not gone well.